‘Walking in the shoes of our patients’: a scoping review of healthcare professionals learning from the simulation of patient illness experiences - Milda Karvelytė (BMC, 2021)
Abstract Background Health professionals who have experienced ill-health appear to demonstrate greater empathy towards their patients. Simulation can afford learners opportunities to experience aspects of illness, but to date, there has been no overarching review of the extent of this practice or the impact on empathic skills. Objective To determine from the evidence—what is known about simulation-based learning methods of creating illness experiences for health professions and the impact on their empathic skills. Study selection Arksey and O’Malley’s methodological framework informed our scoping review of articles relevant to our research question. Three databases (MEDLINE, Embase and Web of Science) were searched, and a sample of 516 citations was screened. Following review and application of our exclusion criteria, 77 articles were selected to be included in this review. Findings Of the 77 articles, 52 (68%) originated from the USA, 37 (48%) of studies were qualitative based and 17 (22%) used a mixed-methods model. Of all the articles in our scope, the majority (87%) reported a positive impact and range of emotions evoked on learners. However, some studies observed more negative effects and additional debriefing was required post-simulation. Learners were noted to internalise perceived experiences of illness and to critically reflect on their empathic role as healthcare providers. Conclusions A diverse range of simulation methods and techniques, evoking an emotional and embodied experience, appear to have a positive impact on empathy and could be argued as offering a complementary approach in healthcare education; however, the long-term impact remains largely unknown.